Answer:
your adding 6 each time so just find the 15th term
Step-by-step explanation:
-3 + 6= 3 and 3+6 = 9
Answer: (3,2)
Step-by-step explanation:
For this set of system of equations, let's use elimination method to find x and y. Let's eliminate y first. In order to do so, the y values have to be the same. Therefore, you multiply the top equation by 3 and the bottom equation by 4.
9x+12y=51
-16x-12y=-72
Now, we can add the 2 equations together for the y to cancel out.
-7x=-21
x=3
Since we know x, we can plug it into any of the equations to find y.
3(3)+4y=17
9+4y=17
4y=8
y=2
With out x and y value, we can put them into an ordered pair. (3,2)
8x+1=-x-1 4-5x=1+6x
8x+x=-1-1 -5x-6x=1-4
9×=-2 -11×=-3
×=-2/9 ×=3/11